2000
DOI: 10.1046/j.1365-232x.2000.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the costs and benefits of information technology in construction

Abstract: Information technology (IT) has been widely applied across many economic sectors in order to increase competitiveness and reduce costs. This paper identifies that uptake of IT within construction is low. It is argued that significant barriers preventing construction organizations from investing in IT include uncertainty concerning the identification and measurement of benefits associated with applications. In particular, it is argued that difficulties in quantifying benefits associated with improved informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…Although the framework captures the complete spectrum of efficiency, effectiveness and business process benefits derived from IT implementation, it provides no answer as to how to combine those three different types of benefits, and most importantly, fails to recognise the difference in perceptions of participants estimating benefits and those measuring them. A more recent framework was proposed to evaluate the informational (savings due to improved quality of project information), automational (savings due to productivity improvement and cost reductions) and transformational (value added through innovation) benefits of IT in construction [22]. Although this particular framework was mainly developed to swerve away from considering subjective benefits evaluation, it utilises probabilistic modelling and simulation techniques, which are purely based on subjective data, to evaluate informational benefits.…”
Section: Framework Perspectivesmentioning
confidence: 99%
“…Although the framework captures the complete spectrum of efficiency, effectiveness and business process benefits derived from IT implementation, it provides no answer as to how to combine those three different types of benefits, and most importantly, fails to recognise the difference in perceptions of participants estimating benefits and those measuring them. A more recent framework was proposed to evaluate the informational (savings due to improved quality of project information), automational (savings due to productivity improvement and cost reductions) and transformational (value added through innovation) benefits of IT in construction [22]. Although this particular framework was mainly developed to swerve away from considering subjective benefits evaluation, it utilises probabilistic modelling and simulation techniques, which are purely based on subjective data, to evaluate informational benefits.…”
Section: Framework Perspectivesmentioning
confidence: 99%
“…Another critical barrier in this research is cost of specialist software too [30] supported that IT systems are too costly that the organisations are unable to affort IT. High cost investment has been one of the most common barrier in ICT adoption [31][32][33][34][35]. Consequently, many construction case studies found that lack of enough training is one of the main barriers to adopting and using IT/ICT applications [33][34][35].…”
Section: Critical Barriers To Implement Ictmentioning
confidence: 99%
“…According to Mitev and March (1998), positive outcomes are facilitated by formality and rigour in IS evaluation, which provides "a scheduled set of occasions for face-to-face communication across multiple levels of hierarchy, thus giving the chance to debate the specific project". Marsh and Flanagan (2000) add that formal evaluation enables the organisation to offer "a clear paper trail, showing the documents submitted at each stage, the minutes of committees and meetings and a record of the point at which capital was officially committed".…”
Section: Formality In Information Systems Investment Evaluation (Isie)mentioning
confidence: 99%